Molecular transport of aromatic solvents through oil palm micro fiber filled nitrile rubber composites. (2019) - Joseph, Shaji; James Jose, Ajith; Wilson, Runcy; Thomas, Sabu; Joseph, Kuruvilla
Abstract: The cellulose micro fiber reinforced nitrile rubber biocomposites were prepared. The effect of chemical treatment on the fiber surface morphology and fiber–rubber interface was investigated using scanning electron microscopy. The transport property through the bio-composites was investigated using aromatic solvents. The effect of chemical treatments on fiber, influence on fiber loading, penetrant size and temperature on the solvent uptake through bio-composites was analyzed. The transport coefficients such as diffusion, permeation and sorption coefficients were estimated by using the van't Hoff relationship and hence the thermodynamic parameters was determined. The first order kinetic rate constant was evaluated and finally the experimental results of diffusion properties were compared with theoretical predictions.